Serum Uric Acid Levels in Schizoaffective Disorder - Aslı Kazgan Kılıçaslan; Sevler Yıldız; Osman Kurt; Sevda Korkmaz (Boğaziçi Tıp Dergisi, 2022)
INTRODUCTION: The level of uric acid (UA) in the blood can indicate the oxidative stress state of the body in some dis-eases. In this study, it was aimed to investigate serum levels of UA in schizoaffective disorder (SD), which attracts attention with its role in oxidant-antioxidant pathways and to compare it with healthy controls. METHODS: The study included 67 patients with SD in remission and 51 healthy controls. Sociodemographic data form and positive and negative syndrome scale (PANSS), young mania rating scale (YMRS), and beck depression inventory (BDI) scale were administered to all participants. Then, venous blood samples were taken from all the participants to study the serum UA levels as well as the routine blood biochemistry parameters. RESULTS: Serum UA levels, PANSS sub-dimensions and total scores, and YMRS and BDI scores of the patients were significantly higher than the control group. There was a significant positive correlation between serum UA levels and PANSS, YMRS, and BDI. DISCUSSION AND CONCLUSION: Serum UA levels of SB patients were found to be higher than healthy controls. This elevation appears as a finding independent of mood episodes or psychotic episodes. The fact that SB patients have higher serum UA during remission periods than healthy controls makes us think that this situation may be specific to the disease itself. Our results can give us a clue about the pathophysiology of SB.